2021
DOI: 10.3389/fphys.2021.739485
|View full text |Cite
|
Sign up to set email alerts
|

Exercise Enhanced Cardiac Function in Mice With Radiation-Induced Heart Disease via the FNDC5/Irisin-Dependent Mitochondrial Turnover Pathway

Abstract: Background: Despite the development of radiation therapy (RT) techniques, concern regarding the serious and irreversible heart injury induced by RT has grown due to the lack of early intervention measures. Although exercise can act as an effective and economic nonpharmacologic strategy to combat fatigue and improve quality of life for cancer survivors, limited data on its application in radiation-induced heart disease (RIHD) and the underlying molecular mechanism are available.Methods: Fifteen young adult male… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Three weeks of moderate-intensity aerobic exercise significantly increased myocardial FNDC5 expression and upregulated serum Irisin expression in irradiated X-ray-induced radiation-induced heart disease (RIHD) mice, significantly upregulated myocardial Drp1, PINK1, and LC3B expression in RIHD mice, promoted mitochondrial fission and mitophagy, and consequently increased mitochondrial protein and ATP content, decreased myocardial inflammatory cytokines infiltration and myocardial fibrosis area, upregulated LVEF, left ventricular end-diastolic dimension (LVEDD), and systolic left ventricular dimension (SLVD), and increased RIHD mice body weight, grip strength and aerobic fitness. This suggests that aerobic exercise may promote mitochondrial fission and mitophagy through the FNDC5/Irisin signaling pathway, thereby restoring cardiac function and aerobic fitness in RIHD mice ( He W. et al, 2021 ). In summary, exercise mediates the regulation of mitophagy by exerkines and delays the development of metabolic diseases.…”
Section: Mitophagy and Exercise Interventionmentioning
confidence: 99%
“…Three weeks of moderate-intensity aerobic exercise significantly increased myocardial FNDC5 expression and upregulated serum Irisin expression in irradiated X-ray-induced radiation-induced heart disease (RIHD) mice, significantly upregulated myocardial Drp1, PINK1, and LC3B expression in RIHD mice, promoted mitochondrial fission and mitophagy, and consequently increased mitochondrial protein and ATP content, decreased myocardial inflammatory cytokines infiltration and myocardial fibrosis area, upregulated LVEF, left ventricular end-diastolic dimension (LVEDD), and systolic left ventricular dimension (SLVD), and increased RIHD mice body weight, grip strength and aerobic fitness. This suggests that aerobic exercise may promote mitochondrial fission and mitophagy through the FNDC5/Irisin signaling pathway, thereby restoring cardiac function and aerobic fitness in RIHD mice ( He W. et al, 2021 ). In summary, exercise mediates the regulation of mitophagy by exerkines and delays the development of metabolic diseases.…”
Section: Mitophagy and Exercise Interventionmentioning
confidence: 99%
“…A 2019 study found that mitophagy, more than macroautophagy, is critical in maintaining cardiac function in diabetic cardiomyopathy [ 99 ]. Although the necessity of exercise-induced mitophagy is not explored in this model, it has been suspected that, in other cardiac injury models, exercise may help maintain cardiac function through upregulating mitophagy [ 100 , 101 , 102 ].…”
Section: Cardiovascular Systemmentioning
confidence: 99%
“…Exercise is the main inducer of irisin secretion both in healthy and dysregulated metabolism individuals (Huh et al, 2015). Studies have confirmed that exercise-induced irisin is correlated with improvement of cardiac function in general (Seo et al, 2020), which partly by modulating autophagy and mitochondrial function (Li et al, 2021a;He et al, 2021). Further previous animal studies report that irisin is implicated in cerebrovascular protective effects of exercise by alleviating ischemic neuron injury (Li et al, 2017;Lourenco et al, 2019).…”
Section: Introductionmentioning
confidence: 97%